Assessing Project Management Maturity to Enhance the Sustainability and Effectiveness of Digital Transformation Initiatives - Yudianingtyas, Deanur; Purwanto, Agustinus Hariadi Djoko (IJOSMAS, 2025)
Digital transformation has become a strategic agenda for organizations to enhance competitiveness, operational efficiency, and long-term sustainability. However, the success of digital transformation projects largely depends on the effectiveness of project management and the organization’s project management maturity level. This study aims to analyze the maturity level of project management and its role in improving the effectiveness and sustainability of digital transformation projects in PT XYZ, a company in the Indonesian telecommunication sector. A mixed-method approach was applied: qualitative data were obtained through Focus Group Discussions (FGDs) with key stakeholders and analyzed using NVivo software, while quantitative analysis utilized secondary company data related to project performance. Project maturity was assessed using the Project Management Maturity Model (PMMM), supported by CMMI and COBIT 2019 frameworks. The results show that PT XYZ’s maturity level is at 2.4 (repeatable–defined), indicating partially defined but insufficiently standardized processes. Key issues include undocumented baseline scope, reactive cost control, unrealistic schedules, and inconsistent quality assurance practices. The findings highlight that maturity level mediates the relationship between project effectiveness and digital transformation success. The study contributes theoretically by integrating maturity level and sustainable project effectiveness within the digital transformation context, and practically by offering strategic recommendations on process standardization, human resource development, digital tool optimization, cost control, governance, and quality assurance.